1999
DOI: 10.1093/bja/82.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide does not alter bispectral index: study with nitrous oxide as sole agent and as an adjunct to i.v. anaesthesia

Abstract: We have studied the effect of nitrous oxide on bispectral index (BIS), calculated from a bipolar encephalogram. Inhalation of 70% nitrous oxide resulted in loss of consciousness in all healthy volunteers (n = 10) but no change in BIS. Brief inhalation up to 1.2% sevoflurane also resulted in loss of consciousness in volunteers (n = 5), but with sevoflurane, BIS decreased. BIS and the haemodynamic effects of adding nitrous oxide were also measured during coronary artery bypass surgery in patients (n = 10) receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(100 citation statements)
references
References 16 publications
5
85
1
8
Order By: Relevance
“…Similar observations that up to 66% N 2 O does not alter the BIS have also been reported. 19 Studies have shown that opioids, 20 as well as nitrous oxide, do not affect BIS values when correlated with drug concentrations and clinical responses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations that up to 66% N 2 O does not alter the BIS have also been reported. 19 Studies have shown that opioids, 20 as well as nitrous oxide, do not affect BIS values when correlated with drug concentrations and clinical responses.…”
Section: Discussionmentioning
confidence: 99%
“…We think that the number of the patients should be greater to detect a difference in induction time. Also, the concentrations of F A /F a not been measured might (23)(24)(25)(26)(27)(28)(29). There are hypotheses that the reason of this is related to N 2 O changing the beta ratio in BIS (the ratio of very high beta activity to the sum of high alpha and beta activities) (23).…”
Section: Discussionmentioning
confidence: 99%
“…В ряде исследований показано, что BIS-алгоритм, эмпирически основанный на ЭЭГ при использовании «ГАМК-ергических» гипнотиков (пропофол), не всегда корректен в отношении общих анестетиков с NMDA-антагонистичными свойствами: кетамина, N2O, α2-адренергических агонистов [15,20,21]. В других литературных источниках указывается на значимое соответствие BIS и клинической картины анестезии ксеноном [11,2,10].…”
Section: Bis-monitoring Use For the Anesthesia And Sedation Level Conunclassified